2011
DOI: 10.1111/j.1600-0579.2011.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing assessment practice through in situ faculty development

Abstract: The aim of this article is to describe the process of an in situ staff development process with the objective to influence change in assessment practice. An in situ training course focusing on writing questions for written examinations, but also including some contextual aspects of assessment practice, was therefore developed and implemented. The anticipated change was measured against Kirkpatrick’s four levels for evaluating training programmes. As a whole, the reaction from the participants was positive (Kir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Knowledge questionnaires Anderson, 2009;Badu, 2013;Grzeskowiak et al, 2015;Haller et al, 2008;Kar et al, 2014;Matsuda et al, 2016;Nestel et al, 2011;Omar et al, 2009;Pickworth and Snyman, 2012;Santos et al, 2012;Sinclair et al, 2015;Tennill, 2011Satisfaction surveys Anderson, 2009Grzeskowiak et al, 2015;Haller et al, 2008;Kar et al, 2014;Lee et al, 2013;Sinclair et al, 2015Rating scales Bylund et al, 2011Haller et al, 2008;Matsuda et al, 2016;Nestel et al, 2011Interviews/discussions Nestel et al, 2011Omar et al, 2009;Pickworth and Snyman, 2012;Tennill, 2011Observation Anderson, 2009Matsuda et al, 2016;Santos et al, 2012Forums Patel et al, 2016Reflective journals Anderson, 2009Lee et al, 2013 does not allow for the consideration of factors other than the training. These limitations have been highlighted in a critical analysis of KM (Bates, 2004).…”
Section: Evaluation Methods Literaturementioning
confidence: 99%
“…Knowledge questionnaires Anderson, 2009;Badu, 2013;Grzeskowiak et al, 2015;Haller et al, 2008;Kar et al, 2014;Matsuda et al, 2016;Nestel et al, 2011;Omar et al, 2009;Pickworth and Snyman, 2012;Santos et al, 2012;Sinclair et al, 2015;Tennill, 2011Satisfaction surveys Anderson, 2009Grzeskowiak et al, 2015;Haller et al, 2008;Kar et al, 2014;Lee et al, 2013;Sinclair et al, 2015Rating scales Bylund et al, 2011Haller et al, 2008;Matsuda et al, 2016;Nestel et al, 2011Interviews/discussions Nestel et al, 2011Omar et al, 2009;Pickworth and Snyman, 2012;Tennill, 2011Observation Anderson, 2009Matsuda et al, 2016;Santos et al, 2012Forums Patel et al, 2016Reflective journals Anderson, 2009Lee et al, 2013 does not allow for the consideration of factors other than the training. These limitations have been highlighted in a critical analysis of KM (Bates, 2004).…”
Section: Evaluation Methods Literaturementioning
confidence: 99%
“…For instance, the teachers perceived that they as a group had also changed their practices in terms of calibrating their teaching and of collaborating more. Such an increase in interaction and support between colleagues has been found to promote change and innovation in teaching and learning . In addition to evaluating faculty development activities on the basis of changes related to the individual teacher and to the learning environment, Kirkpatric also notes that such activities may be evaluated on the basis of changes in students' learning strategies and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent perspectives on learning tend to view teaching not just as individual practice, but also as part of collaborative group processes with opportunities for mutual support. These should in turn affect the aims and activities of faculty development .…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, in relation to the skills required to teach and assess in a CBME program, studies have revealed that faculty development can improve skills in direct observation, with changes in behaviour persisting up to eight months, 8 as well as elicit changes in assessment practice. 9 What is CBME?…”
Section: What Is Faculty Development?mentioning
confidence: 99%